The Rules of Engagement: Richard Taruskin and the History of Western Music - White, Harry (Journal of the Society for Musicology in Ireland, 2007)
The Oxford History of Western Music (2005) is a scrutiny of the ‘literate tradition’ of music in European and North American culture from the beginnings of notation to the end of the twentieth century. Richard Taruskin’s monumental and profoundly erudite engagement with a thousand years of western art music is animated from the outset by a radical critique of German idealism and the influence which this has exerted on the formation and transmission of European and American musical thought. Taruskin takes the view that as a result of this influence, the history of music has been seriously distorted, especially in regard to the contractual intelligibility of musical discourse in relation to society. The prestige of progressivism, as this is manifested in atonal and serial composition, in primitivism and neoclassicism, has enjoyed an excessive pre-eminence which eclipses in turn the narrative clarity of tonal music in the twentieth century. In this review essay, Taruskin’s indictment of historicism as a primary agent in the perpetuation of (German and Anglo-American) musicological orthodoxy is appraised in the context of his own obligations to narrative, musical analysis and the reception history of musical works. Taruskin’s identification of an historicist ‘master-narrative’ in earlier surveys of western music is considered in relation to a new master- narrative, of Taruskin’s own making, which condemns the hegemony of musical idealism at every turn. The tension which arises between this enduring preoccupation and the author’s sustained engagement with individual musical texts tends to confirm the autonomy of the musical work, not as an object immune (or indifferent) to history, but as a nexus of social, ideological and political expression which attains to a self-standing aesthetic integrity.